PELETAKAN HAK ATAS TANAH TERHADAP HAK PENGELOLAAN BERDASARKAN PP NOMOR 18 TAHUN 2021 : a) Bagaimana Ketentuan Hukum Peletakan Hak Atas Tanah terhadap Hak Pengelolaan? b) Bagaimana Prosedur Peletakan Hak Atas Tanah terhadap Hak Pengelolaan berdasarkan PP No. 18 Tahun 2021? - m.bahri al soddik (Jurnal Hukum Lex Generalis, 2024)
PTPN II is collaborating with PT Ciputra Group to change the function of the land into an elite residential property business project, with home ownership status using HGB, not SHM. If the HGU validity period expires and is not extended, then what is the ownership status of the house that has been purchased, considering that the ownership status of the house is HGB, not SHM? If the HGB above the HPL has expired, the Management Rights holder will regain the rights to the land, while the Ownership Rights Certificate related to the Building Use Rights will also expire or no longer be valid. In writing this journal, researchers using normative juridical methods will study various laws and regulations, theories and provisions that are relevant to the problem being analyzed.